The Effect of an Enamel Matrix Derivative (Emdogain) Combined with Bone Ceramic on Bone Formation in Mandibular Defects: A Histomorphometric and Immunohistochemical Study in the Canine. (24th April 2012) - Birang, Reza; Shah Abouei, Mohammad; Mohammad Razavi, Sayed; Zia, Peyaman; Soolari, Ahmad
Abstract : Background . The purpose of this study was to evaluate the combination of an enamel matrix derivative (EMD) and an osteoconductive bone ceramic (BC) in improving bone regeneration. Materials and Methods . Four cylindrical cavities (6 × 6 mm ) were prepared bilaterally in the mandible in three dogs. The defects were randomly assigned to four different treatments—filled with EMD/BC and covered with a nonresorbable membrane, filled with EMD/BC without membrane, membrane coverage only, or control (left untreated)—and healed for 2, 4, or 6 weeks. Harvested specimens were prepared for histologic, histomorphometric, and immunohistochemical analyses. Results . Sites treated with EMD/BC with or without membrane showed more total bone formation and lamellar bone formation than membrane-only and control defects. There were no statistically significant differences in total bone formation between EMD/BC with or without membrane. Conclusion . EMD with BC might improve bone formation in osseous defects more than membrane coverage alone; the use of a membrane had no significant additive effect on total bone formation.